Anagogical Level of Russian Classical Literature: Problems of Small and Large Eschatology in the Novel “Brothers Karamazov” by F. M. Dostoyevsky - Irina V. Dergacheva (Два века русской классики)
The new concept of the history of Russian literature presupposes a hermeneutic reading of the texts of classics, allowing us to understand the hidden meanings embedded in them, reflecting the Christian foundation of Russian culture. The need to look at the work of Russian writers of the 19th century as a reflection of a unique discourse of precedent Christian texts poses the need for teachers and lecturers of literature to master additional educational programs on the “Spiritual and Moral Foundations of Russian Literature.” This article provides an analysis of the images of small and large eschatology in the last novel of the Great Pentateuch by F. M. Dostoevsky, reflecting the axiological views of the writer. The research demonstrates that the content of Dostoevsky’s last novel contains the spiritualizing and enlightening power of Christian life-building for the world.